Radiation hardened CMOS design - Di, Jiwei (2019)
Nowadays, human beings have stepped into space era gradually. However, space environment is highly radioactive, which means electronic devices will suffer from space-radiation effect, especially most modern semiconductor electronic elements are vulnerable to radiation damage. It is obviously that a little bit of instability of equipment in out-space may cause disaster and the lack of high-performance radiation-hardened chips used in space is already lag behind the most recent development. So, in this dissertation project I am trying to design a high-performance radiation-hardened chips used in space.